Song determined by phylogeny and body mass in two differently constrained groups of birds: manakins and cardinals - Natália S. Porzio; Angelica Crottini; Rafael N. Leite; Paulo G. Mota (BMC Ecology and Evolution, 2024)
Abstract The songs of birds are complex signals that may have several functions and vary widely among species. Different ecological, behavioural and morphological factors, as well as phylogeny, have been associated as predictors of the evolution of song structure. However, the importance of differences in development, despite their relevance, has seldom been considered. Here, we analysed the evolution of song in two families of songbirds that differ in song development, manakins (suboscines) and cardinals (oscines), with their phylogeny, morphology, and ecology. Our results show that song characteristics had higher phylogenetic signal in cardinals than in manakins, suggesting higher evolutionary lability in the suboscines. Body mass was the main predictor of song parameters in manakins, and together with habitat type, had a major effect on cardinals’ song structure. Precipitation and altitude were also associated with some song characteristics in cardinals. Our results bring unexpected insights into birdsong evolution, in which non-learners (manakins) revealed greater evolutionary lability than song learners (cardinals).